MicroRNA-1246 Mediates Drug Resistance and Metastasis in Breast Cancer by Targeting NFE2L3 - Yue-chu Dai; Yin Pan; Ming-ming Quan; Qi Chen; Yue Pan; Yan-yun Ruan; Jian-guo Sun; Jian-guo Sun (Frontiers in Oncology, 2021)
MicroRNA (miR)-1246 is abnormally expressed and has pro-oncogenic functions in multiple types of cancer. In the present study, its functions in breast cancer and the underlying mechanisms were further elucidated. The clinical relevance of miR-1246 was analyzed and its expression in clinical specimens and cell lines was examined by reverse transcription-quantitat000000ive PCR analysis. FACS was used to detect cell apoptosis and mitochondrial transmembrane potential. A Transwell system was used to detect cell migration and invasion. Luciferase assay was used to confirm the target gene of miR-1246. Xenograft and metastasis mouse models were constructed to determine the function of miR-1246 in vivo. miR-1246 was found to be negatively associated with overall survival in breast cancer. miR-1246 inhibitor could effectively increase the cytotoxicity of docetaxel (Doc) by inducing apoptosis, and impair cell migration and invasion by suppressing epithelial-to-mesenchymal transition. Nuclear factor (erythroid 2)-like factor 3 (NFE2L3) was confirmed as a new target gene of miR-1246, and its overexpression was shown to reduce drug resistance and migration of MDA-MB-231 cells. More importantly, NFE2L3-silencing attenuated the effect of miR-1246 inhibitor. Finally, the inhibition of miR-1246 effectively enhanced the cytotoxicity of Doc in xenografts and impaired breast cancer metastasis. Therefore, miR-1246 may promote drug resistance and metastasis in breast cancer by targeting NFE2L3.